Corrosion‐fatigue behaviour of Cr–Mo steel under biaxial tension. Issue 11 (24th June 2020) - Gaur, Vidit; Doquet, Véronique; Persent, Emmanuel; Roguet, Eléonore
Abstract: Combined cyclic tension and internal pressure tests with various proportions of each loading were run on a 2.5%Cr–1%Mo steel in air and in 3.5% NaCl solution, with and without cathodic protection to investigate the effect of positive stress biaxiality on corrosion‐fatigue lives and damage mechanisms. At free potential, a strong reduction in fatigue resistance was observed for uniaxial as well as for equibiaxial cyclic tension and attributed to multiple crack initiation from corrosion pits. Cathodic protection completely cancelled the detrimental effect of the corrosive environment on fatigue lives whatever the load biaxiality was, in spite of an obvious enhancement of intergranular fracture attributed to hydrogen embrittlement.